Geopolitics and Post-Structuralism: Th e Prospects for Integration - A. M. Kuchinov (Сравнительная политика)
Quite recently in Great Britain “post-giddensian” sociology has been mentioned as one of the latest development trends of contemporary sociological theory. Nevertheless, the spread of contemporary British post-structuralist theories is rather limited in Russia. Nowadays geopolitics has retreated from outdated sociological theories such as naturalistic reductionism, but the tendency to employ sociological theories in geopolitics exists. Th is article seeks to understand the possible ways of implementing contemporary British post-structuralism in geopolitical research.